2019
DOI: 10.1002/ijc.32231
|View full text |Cite
|
Sign up to set email alerts
|

The preventable burden of breast cancers for premenopausal and postmenopausal women in Australia: A pooled cohort study

Abstract: Estimates of the future breast cancer burden preventable through modifications to current behaviours are lacking. We assessed the effect of individual and joint behaviour modifications on breast cancer burden for premenopausal and postmenopausal Australian women, and whether effects differed between population subgroups. We linked pooled data from six Australian cohort studies (n = 214,536) to national cancer and death registries, and estimated the strength of the associations between behaviours causally relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…There are few other efforts in the literature to describe the complexity of etiologic factors in breast cancer. However, a recent study that pooled six cohort studies from Australia reported on the strength of modifiable behavioral risk factors with a focus on prevention at population levels (162). By using population attributable fractions they identified alcohol as the leading modifiable risk factor for premenopausal women and obesity and alcohol consumption as the most modifiable factors for postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…There are few other efforts in the literature to describe the complexity of etiologic factors in breast cancer. However, a recent study that pooled six cohort studies from Australia reported on the strength of modifiable behavioral risk factors with a focus on prevention at population levels (162). By using population attributable fractions they identified alcohol as the leading modifiable risk factor for premenopausal women and obesity and alcohol consumption as the most modifiable factors for postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the Million Women Study 135 . A large prospective pooled Australian cohort, Arriaga et al, 2019 136 have recently shown that regular alcohol consumption is the leading modifiable cause of BC burden for premenopausal women, explaining 12.6% of BCs.…”
Section: Alcoholmentioning
confidence: 99%
“…older premenopausal women with a strong family history of the disease) the increase in absolute risk is likely to be of more importance. In fact, it has been estimated that 7% of BC burden for premenopausal women is owing to the use of hormonal contraceptives for 5 or more years 136 . US statistics indicate that as much as 10% of OCP users are older premenopausal women aged 40-49 286 .…”
Section: The Role Of Exogenous Hormones In Breast Cancer Riskmentioning
confidence: 99%
“…For example, in Australia, it has been estimated that any regular consumption of alcohol accounts for 12.6% and 6.6% of premenopausal and postmenopausal breast cancer, respectively. 84 Alcohol consumption accounts for 12% of breast cancer in the United Kingdom. 11 In the United Kingdom, regular consumption of each additional drink per day accounts for 11 additional breast cancers per 1,000 women in their lifetime, up to age 75.…”
Section: Recommendationsmentioning
confidence: 99%